An instrument to measure students’ readiness for embedded system design course - Ridwan Saeed, Intisar Ibrahim (2019)
Embedded Systems Design has emerged as one of the fastest growing areas in the world. In this regard, higher education institutions acknowledge the significance for offering Embedded Systems Design course to fulfil the needs of skilled human resources in the field. Unfortunately, being a highly difficult and specialized course, it requires students to have sufficient body of knowledge courses in both theory and practice. To address this issue, this study proposed an instrument to measure students’ readiness for Embedded Systems Design course. The study was conducted using a sequential exploratory mixed method design. First, a survey instrument named MeSRESD which consisted of 10 scales and 89 items was developed. MeSRESD assessed students’ cognitive, affective, and psychomotor skills through holistic assessment by taking into account the domains of technical skills, critical thinking skills, communication skills, team working skills, entrepreneurship skills, lifelong learning skills, level of interest, attitude, and prior experience. Content validity of MeSRESD was verified using content validity index (CVI) and content validity ratio (CVR). All MeSRESD scales showed CVI and CVR ranging from 0.92 to 1.00 and from 0.88 to 1.00 respectively, establishing an excellent content validity. A pilot study on 40 students was performed to assess the Cronbach’s alpha scale reliability. The results obtained were from 0.73 to 0.92 using Statistical Package for Social Sciences (SPSS 23.0) and from 0.70 to 0.99 using WINSTEPS 3.92.1, indicating an excellent internal consistency reliability. MeSRESD construct validity was established using Rasch Analysis and WINSTEPS 3.92.1. The results showed that all scales fitted the Rasch measurement model with acceptable fit index from 0.6 to 1.4 and demonstrated excellent consistency, with a reliability index from 0.97 to 0.99 for items and from 0.70 to 0.88 for persons. The unidimensionality of each MeSRESD scales was evaluated using principal component analysis. Based on these results, we concluded that the survey instrument was valid and reliable. MeSRESD was administered in nine universities in Malaysia, Sudan, and Saudi Arabia. A total of 415 questionnaires with a response rate of 97.4% were analysed. Based on the literature review, the readiness threshold of 3.40 was selected. However, the students’ mean scores of MeSRESD scales were from 2.47 to 2.89, which were lower than the threshold. In light of these results, the study revealed strong evidence that students lack prior knowledge and had poor understanding of Embedded Systems Design course. They possessed poor proficiency in critical thinking, communication, team working, entrepreneurship, and lifelong learning skills. In addition, they had low level of interest, lack of prior experience and had negative attitude towards learning Embedded Systems Design course. Therefore, there is a need for universities to address this issue and take remedial action to improve the chance of academic success for the students not only in Embedded Systems Design course, but also in other related courses.